Research and application of micropower safety monitoring IoT system for mine - Da ZHANG; Jinong WANG; Hu JI; Hao JI; Yunfeng ZHAO (Tongxin xuebao)
In view of the problems existing in the safety monitoring system of China’s mining enterprises,such as poor reliability,small coverage,high cost,weak maintenance and inaccurate early-warning,etc.,a new safety monitoring IoT system with micro power consumption was proposed for Chinese mines to provide effective technical support for the safety of mine production and operation.The key technologies such as micro-power consumption information collection,fault diagnosis and auto-recovery,energy-saving wireless communication,online intelligent data analysis and early warning had been broken through by the proposed system,which had been successfully applied in typical cases such as online monitoring of tailings ponds,open-pit slop and ground pressure of domestic mining enterprises.Field practice shows that the proposed system is more suitable for mine operation conditions than the existing conventional safety monitoring system,the SNR of new sensor is increased by 1.4 times,the comprehensive energy consumption is reduced by 10%,which is suitable for online intelligent analysis and rapid warning.